2018
DOI: 10.1017/s1041610218001059
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social network on the physical activity—cognitive function nexus in late life

Abstract: Vigorous physical activity is, indeed, related to subsequent cognitive functioning. However, the relationship is tempered by social network size. Therefore, interventions that increase both social connectedness and physical activity, especially among older people who are isolated and sedentary, are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Moreover, according to the study by Seeman et al (Seeman et al., 2011), being exposed to negative social interactions like excessive criticism or conflict may result in a decline in executive function but not episodic memory. Notably, Litwin et al (Litwin & Shaul, 2019) also found that increased social network size boosts the effect of physical activity on cognitive function in old age. Also, the results of a recent study on a sample of 31,954 European healthy elderlies, indicated that being satisfied in one's social life and engaging in different forms of social activities, significantly affected cognitive function in elderly participants, prospectively (Miceli et al., 2019).…”
Section: Social Engagementmentioning
confidence: 99%
“…Moreover, according to the study by Seeman et al (Seeman et al., 2011), being exposed to negative social interactions like excessive criticism or conflict may result in a decline in executive function but not episodic memory. Notably, Litwin et al (Litwin & Shaul, 2019) also found that increased social network size boosts the effect of physical activity on cognitive function in old age. Also, the results of a recent study on a sample of 31,954 European healthy elderlies, indicated that being satisfied in one's social life and engaging in different forms of social activities, significantly affected cognitive function in elderly participants, prospectively (Miceli et al., 2019).…”
Section: Social Engagementmentioning
confidence: 99%
“…Some older adults may have maintained functional capacity through continued exercise, despite restrictions on physical and social engagement 14 . For others, mobility and physical conditioning may have declined due to increased social isolation and sedentary behaviors, leading to higher risk for injuries such as falls 1–5 …”
Section: Introductionmentioning
confidence: 99%
“…Further, we standardized the estimates to compare the strength of the associations among social network properties. The confounders were selected by reviewing prior studies ( 8 , 33 , 34 ). Model 1 was adjusted for age and model 2 was additionally adjusted for socioeconomic factors.…”
Section: Methodsmentioning
confidence: 99%